The Effect of Strength of Auditing and Accounting Standards and Corporate Governance on Economic Growth: A Case Study of the Islamic World - Talalweh, Mohammad; Samara, Wisam (Finance and Business Economies Review, 2020)
The purpose of this paper is to determine the effect of corporate governance on the economic growth of Muslim countries and demonstrate that the Strength of Auditing and Accounting Standards is the most crucial component of corporate governance and thus has the most effect on economic growth. We will use the Strength of Auditing and Accounting Standards, Conflict of Interest Regulation, and Shareholders Governance to determine the level of corporate governance. The data was collected from the Global Competitiveness Index 4 for 2019 and the World Bank for the Muslim countries for the year 2019. The Least Squares Regression analysis is used to determine the effect of corporate governance on the GDP per Capita for a number of Muslim countries. Our analysis had indicated that one unit increase in corporate governance results in a 0.05 unit increase in the GDP per Capita. Our analysis had also indicated that a one unit increase in Strength of Auditing and Accounting Standards results in a 0.06 unit increase in the GDP per Capita. Thus both corporate governance and Strength of Auditing and Accounting Standards have a positive effect on economic growth for Islamic world.